Aerodynamic analysis of insect-like flapping wings in fan-sweep and parallel motions with the slit effect - Zhu, Zenggang; Zhao, Jingtai; He, Yuanyuan; Guo, Shijun; Chen, Si; Ji, Bing (Elsevier, 2022)
In this study, the aerodynamic performance of flapping wings using a parallel motion was investigated and compared with the insect-like “fan-sweep” motion, and the effect of adding a slit to the wings was analyzed. First, numerical simulations were performed to analyze the wing aerodynamics of two flapping motions with equivalent stroke amplitudes over a range of pitching angles based on computational fluid dynamics (CFD). The simulation results indicated that flapping wings with a rapid and short parallel motion achieved better lift and efficiency than those of the fan-sweep motion while maintaining the same aerodynamic characteristics regarding stall delay and leading-edge vortices. For a parallel motion with a pitching angle of 25° and 100 mm stroke amplitude, the wings generated an average lift of 8.4 gf with a lift-to-drag ratio of 1.06, respectively, which were 1.8% and 26% greater than those of the fan-sweep motion with a corresponding 96° stroke amplitude. This situation was reversed when the pitching angle and stroke amplitude were increased to 45° and 144° for the fan-sweep motion, which was equivalent to the parallel motion with a 150 mm stroke amplitude. The slit effect in the parallel motion was also evaluated, and the CFD results indicated that a slit width of 1 mm (1/50 wing chord) increased the lift of the wing by approximately 27% in the case of the 150 mm stroke amplitude. Further, the slit width slightly influenced the lift and aerodynamic efficiency.
Keywords: Insect-like flapping wings; Aerodynamic efficiency; Fan-sweep; Parallel flapping motion; Wing slit